Molecular basis of inherited calcium channelopathies: role of mutations in pore-forming subunits - Mckeown Lynn; Robinson Philip; Jones Owen T (Acta Pharmacologica Sinica, 2016)
The pore-forming alpha subunits of voltage-gated calcium channels contain the essential biophysical machinery that underlies calcium influx in response to cell depolarization. In combination with requisite auxiliary subunits, these pore sub-units form calcium channel complexes that are pivotal to the physiology and pharmacology of diverse cells ranging from sperm to neurons. Not surprisingly, mutations in the pore subunits generate diverse pathologies, termed channelopathies, that range from failures in excitation-contraction coupling to night blindness. Over the last decade, major insights into the mechanisms of pathogenesis have been derived from animals showing spontaneous or induced mutations. In parallel, there has been considerable growth in our understanding of the workings of voltage-gated ion channels from a structure-function, regulation and cell biology perspective. Here we document our current understanding of the mutations underlying channelopathies involving the voltage-gated calcium channel alpha subunits in humans and other species.